An extraordinary deceased child due to the Hurler-Scheie syndrome - Yannelis Martínez Yero; Dulce María Echavarría Estenoz (Centro Provincial de Información de Ciencias Médicas, 2016)
The personal experience of a mother that faced the Hurler-Scheie syndrome, strange disease suffered from his son already deceased, is exposed with the purpose to demonstrate that the observation of the changes occurring in a child, is vital for his development. The care toward a young child with this disorder is indispensable to achieve a childhood with life quality; therefore, the Cuban health system should continue designing strategies that guarantee an early diagnosis and the possibility of opportune therapeutic alternatives as the enzymatic substitution therapy.